Factors Associated With In-hospital Mortality of Children With Acute Fulminant Myocarditis on Extracorporeal Membrane Oxygenation - Lee, En-Pei; Chu, Sheng-Chih; Huang, Wun-Yan; Hsia, Shao-Hsuan; Chan, Oi-Wa; Lin, Chia-Ying; Su, Ya-Ting; Chang, Yu-Sheng; Chung, Hung-Tao; Wu, Han-Ping; Lin, Jainn-Jim (Frontiers in Pediatrics, 2020)
Aim: To analyze the factors associated with in-hospital mortality of children with acute fulminant myocarditis on venoarterial extracorporeal membrane oxygenation (VA-ECMO). Methods: This was a retrospective cohort study using chart reviews of patients diagnosed with acute fulminant myocarditis at the pediatric intensive care unit of two tertiary medical centers between January 1, 2005 and December 31, 2017. The inclusion criteria for this study were: (1) age from 1 month to 18 years; (2) diagnosed with acute myocarditis; (3) cardiogenic shock and need vasoactive-inotropic score ≥20 within 48 h after the use of vasoactive-inotropic agents; and (4) the need for ECMO placement. Results: Thirty-three children with acute fulminant myocarditis who needed ECMO were included. Clinical parameters were retrospectively reviewed. The overall survival rate was 69.6%. Higher levels of pre-ECMO troponin-I and pre-ECMO lactate, and lower post-ECMO left ventricular ejection fraction (LVEF) were significantly associated with in-hospital mortality in univariate analysis. Only higher pre-ECMO lactate and lower post-ECMO LVEF remained as predictors for in-hospital mortality in multivariate analysis. The areas under the curve of pre-ECMO lactate and post-ECMO LVEF in predicting survival were 0.848 (95% CI, 0.697–0.999, p = 0.002) and 0.824 (95% CI, 0.704–0.996, p = 0.01), respectively. A pre-ECMO lactate level of 79.8 mg/dL and post-ECMO LVEF of 39% were appropriate cutoff points to predict mortality. Conclusion: Pre-ECMO lactate level was associated with mortality in children with acute fulminant myocarditis, with an optimal cutoff value of 79.8 mg/dL. After VA-ECMO implantation, post-ECMO LVEF was associated with mortality, with an optimal cutoff value of 39%. The use of LVADs or urgent heart transplantation should be considered if the post-ECMO LVEF does not improve.